2008
DOI: 10.3858/emm.2008.40.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoid-phospholipid complex induces apoptosis in mammary epithelial cells by STAT-3 signaling

Abstract: Curcumin (from the rhizome of Curcuma longa) is well documented for its medicinal properties in Indian and Chinese systems of medicine where it is widely used for the treatment of several diseases. Epidemiological observations are suggestive that curcumin consumption may reduce the risk of some form of cancers and provide other protective biological effects in humans. These biological properties have been attributed to curcuminoids that have been widely studied for their anti-inflammatory, anti-angiogenic, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…When used as a pre-treatment, curcumin inhibits interferon-gamma-induced phosphorylation of nuclear STAT1 and -3 [ 63 , 64 ]. Similar suppression of STAT3 activation was also observed in Hodgkin’s lymphoma [ 52 ], T-cell leukemia [ 65 ], head and neck squamous cell carcinoma [ 66 ], multiple myeloma cells [ 52 , 67 ] and in CD138 + cells derived from multiple myeloma patients [ 45 ] following curcumin treatment but also after treatment with curcumin analogs such as GO-Y030 [ 68 ], FLLL1 and FLLL12 [ 69 ] or a curcumin-phospholipid complex [ 70 ]. The interferon-a-induced activation of STAT1 was also inhibited by curcumin in human lung A549 carcinoma and melanoma cells [ 71 ].…”
Section: Signaling Pathways Affected By Curcumin Treatmentmentioning
confidence: 56%
“…When used as a pre-treatment, curcumin inhibits interferon-gamma-induced phosphorylation of nuclear STAT1 and -3 [ 63 , 64 ]. Similar suppression of STAT3 activation was also observed in Hodgkin’s lymphoma [ 52 ], T-cell leukemia [ 65 ], head and neck squamous cell carcinoma [ 66 ], multiple myeloma cells [ 52 , 67 ] and in CD138 + cells derived from multiple myeloma patients [ 45 ] following curcumin treatment but also after treatment with curcumin analogs such as GO-Y030 [ 68 ], FLLL1 and FLLL12 [ 69 ] or a curcumin-phospholipid complex [ 70 ]. The interferon-a-induced activation of STAT1 was also inhibited by curcumin in human lung A549 carcinoma and melanoma cells [ 71 ].…”
Section: Signaling Pathways Affected By Curcumin Treatmentmentioning
confidence: 56%
“…Curcumin is a known inducer of apoptosis in different types of normal and tumoral cells. [42][43][44][45][46][47][48][49] Importantly, previous studies showed that curcumin may induce apoptosis in EBV-immortalized lymphoblastoid cells. 50 Thus, we first corroborated the proapoptotic properties of curcumin in CL-45 cells and found that the phytochemical induced cell death in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out on rhizome of C. domestica, C. longa, C.xanthorrhiza, and C. zedoaria shows the presence of curcumin derivatives and sesquiterpen compounds (Cucuzza, Motta, Miretti, Accornero, & Baratta, 2008). Curcuminoids contained in several species depending on the type of species.…”
Section: Introductionmentioning
confidence: 99%